PEMAHAMAN TENTANG PENDIDIKAN ANAK DALAM LINGKUNGAN KELUARGA BERDASARKAN SURAT LUQMAN AYAT 12-19 AL-QUR'AN (STUDI KRITIS TAFSIR AL-MARAGHI) - Maulana, Taufik; Ulpah, Ghina; Afifah, Nurul; Permana, Gilang Sukma; Rif'atunnabilah, Khasna; Abdulah Pakarti, Muhammad Husni (IMTIYAZ: Jurnal Ilmu Keislaman, 2023)
Educating children in this age of globalization is not as easy as imagined, so many problems and problems faced by educators and parents. It can be seen in the age of globalization has a huge impact / influence on the lives of mankind, especially among students from various aspects of life. This study aims to determine the concept of child education in the family according to the Qur'an letter Luqman verses 12-19. The method used in this research is library research with a qualitative approach. The method of data collection in this study by using data sources, education books, moral education, the internet, journals that have the same discussion, and other information related to this research, text and discourse analysis. After the data is collected, data analysis will be carried out to find the essence of this research. Based on the results of the research, it is concluded that children's education in the family is very important, the family becomes the foundation for the formation of children's behavior, with the guidance of Surah Luqman verses 12-19 can help in educating children. There are four aspects, namely tawhid education, worship education, moral education and social education. The results of this study are very important, children are a mandate so it is appropriate to be loved, guarded and cared for, so by instilling education is a way of protecting children. Education is not only providing education but must be able to embed in children praiseworthy attitudes and behavior. Education is very useful that we can instill in our children according to Luqman's message, this message is so useful for us. The family as educators who will provide the foundation for children. Whoever we are parents, teachers, educators must be able to be a good role model.